METHODOLOGY FOR DIAGNOSING THE MASTERING OF PRIMARY GRADE STUDENTS' SKILLS FOR ACTIVITY (Web of Technology: Multidimensional Research Journal, 2024)
The article discusses the practice-oriented methods of diagnosing the mastering of primary school students' skills for mastering knowledge, mastering the foundations of education, and diagnosing their skills for preparing for practical activity.